NOSH-aspirin (NBS-1120), a dual nitric oxide and hydrogen sulfide-releasing hybrid, reduces inflammatory pain - Fonseca, Miriam D (Pharmacol Res Perspect, 2015)
The development of nitric oxide (NO)- and hydrogen sulfide (H(2)S)-releasing nonsteroidal anti-inflammatory drugs (NSAIDs) has generated more potent anti-inflammatory drugs with increased safety profiles. A new hybrid molecule incorporating both NO and H(2)S donors into aspirin (NOSH-aspirin) was recently developed. In the present study, the antinociceptive activity of this novel molecule was compared with aspirin in different models of inflammatory pain. It was found that NOSH-aspirin inhibits acetic acid-induced writhing response and carrageenan (Cg)-induced inflammatory hyperalgesia in a dose-dependent (5–150 μmol/kg, v.o.) manner, which was superior to the effect of the same doses of aspirin. NOSH-aspirin’s antinociceptive effect was also greater and longer compared to aspirin upon complete Freund’s adjuvant (CFA)-induced inflammatory hyperalgesia. Mechanistically, NOSH-aspirin, but not aspirin, was able to reduce the production/release of interleukin-1 beta (IL-1β) during Cg-induced paw inflammation. Furthermore, NOSH-aspirin, but not aspirin, reduced prostaglandin E(2)-induced hyperalgesia, which was prevented by treatment with a ATP-sensitive potassium channel (K(ATP)) blocker (glibenclamide; glib.). Noteworthy, the antinociceptive effect of NOSH-aspirin was not associated with motor impairment. The present results indicate that NOSH-aspirin seems to present greater potency than aspirin to reduce inflammatory pain in several models. The enhanced effects of NOSH-aspirin seems to be due to its ability to reduce the production of pronociceptive cytokines such as IL-1 β and directly block hyperalgesia caused by a directly acting hyperalgesic mediator in a mechanism dependent on modulation of K(ATP) channels. In conclusion, we would like to suggest that NOSH-aspirin represents a prototype of a new class of analgesic drugs with more potent effects than the traditional NSAID, aspirin.